If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7(4-3x+12(x-5)x8)=-7(x+5)+2x
We move all terms to the left:
7(4-3x+12(x-5)x8)-(-7(x+5)+2x)=0
We calculate terms in parentheses: -(-7(x+5)+2x), so:We get rid of parentheses
-7(x+5)+2x
We add all the numbers together, and all the variables
2x-7(x+5)
We multiply parentheses
2x-7x-35
We add all the numbers together, and all the variables
-5x-35
Back to the equation:
-(-5x-35)
7(4-3x+12(x-5)x8)+5x+35=0
We add all the numbers together, and all the variables
5x+7(4-3x+12(x-5)x8)+35=0
We move all terms containing x to the left, all other terms to the right
5x+7(4-3x+12(x-5)x8)=-35
| 7-4n=51 | | 25(x+10)=525 | | -4.5p=-60.3 | | (x+60)+(x+136)=180 | | 7(43x+12(x-5)x8)=-7(x+5)+2x | | 2g-10=150 | | 5=n^2 | | (x+22)+(x+22)+(x)+(x)+(90)+(90)=180 | | 15-4k=-6k+5 | | 5x+-6=8+-2x | | x^2+11x-306=0 | | 2(y−1)+6y = −10 | | 0=-4b+2b | | 9-5(11x+7)=0 | | 6x+2=-26 | | t/2=-24 | | 6x-12=8x+14 | | 10-3w=14-7w | | 228/5=x/2 | | 0.25/3=x/11/2 | | 4+p/5=6 | | (16x-1)+(-5+x)=180 | | 64c^2=81 | | 0.25÷3=x÷11/2 | | 7(8x-3)=91 | | 6d−2/11=2d−2/13 | | -4-3k=26 | | 4(x+6)/3=2x-5 | | 6d−2/11=2d−2/13 | | 8z-7-3z=7+5z | | 3y-18=24 | | 6d−2÷11=2d−2÷13 |